Analysis of Spatial Utilization in Coastal Areas: A Case Study of East Flores Regency, East Adonara District, Lamahala Jaya Village - Anisa Suriyani Abbas; Hamza H. Wulakada; Henda V. R. Taopan (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
The East Flores Regency Spatial Plan for 2007-2027, as outlined in East Flores Regency Regulation Number 13 of 2008, aims to achieve balanced regional development between coastal and inland areas. This balanced development aims to improve the quality of life for the community through the appropriate and efficient use of space, such as coastal areas and rice fields, to support food security and sustainable coastal management. This study aims to: (1) Determine the utilization of coastal space in Lamahala Jaya Village, East Adonara District, East Flores Regency. (2) Determine the impact of the utilization of coastal space in Lamahala Jaya Village, East Adonara District, East Flores Regency. This research method is descriptive quantitative. The results of the study indicate that (1) The utilization of space in the coastal area of Lamahala Jaya Village in the economic and social categories is 0.912402 Ha and the largest area of ​​space utilization in the coastal area is settlements. Meanwhile, the unused space in the coastal area in Lamahala Jaya Village is 0.937454 Ha. (2) The impact of coastal space utilization in Lamahala Jaya Village is land subsidence with a ratio of 0.00546 Ha. Therefore, a comprehensive evaluation and re-organization of the current spatial utilization patterns is very urgent and crucial to implement.